The Effect of Workload and Compesation on Employee Performance With Work Stress as an Interving Variable in KSOP Class III Tanjung Wangi, Banyuwangi Regency - Ika Setia Ajeng Prabintari (Journal of Management, 2025)
Performance problems that occurred at KSOP III Tanjung Wangi include the leadership always prioritizing quality work in encouraging their employees, still there are jobs that cannot be completed without improvement, still there are employees that have not completed the work in accordance with the set time, lack of supervision from superiors and still poor relationships between employees. The purpose of this study is to find out and measure the effect of workload and compensation on employee performance with work stress as an intervening variable in KSOP III Tanjung Wangi. The object of the study was all civil servants at KSOP III Tanjung Wangi. The population taken in this study based on the above theory is 93 employees at KSOP III Tanjung Wangi. The author uses a saturated sampling method, so sampling from the total population of 93 people at KSOP III Tanjung Wangi. In this study the data analysis technique used is Partial Least Square (PLS) using the WarpPLS 8.0 application. Partial Least Square to handle many variables of response/bound/dependent variables as well as explanatory variables at once. The results of the test proved that (1) there was a significant effect on Work Stress (Z), (2) there was a significant effect on Compensation (X2) on Work Stress (Z), (3) there was a significant effect on Work Load (X1) on Workforce Performance (Y), (4) there was a significant effect on Workforce Performance (X2), (4) there was a significant effect on Workforce Performance, (5) there is a significant effect that Work Stress (Z) on Employee Performance (Y), (6) Work Stress (Z) may mediate the effect of Workload (X1) on Employee Performance (Y), (7) Work Stress (Z) cannot mediate the effect of Compensation (X2) on Performance.